Animal Handling Practice Among Rural Households in Northwest Ethiopia Increases the Risk of Childhood Diarrhea and Exposure to Pathogens From Animal Sources - Zemichael Gizaw; Alemayehu Worku Yalew; Bikes Destaw Bitew; Jiyoung Lee; Michael Bisesi (SAGE Publishing, 2024)
Background: In Ethiopia, domestic animals and their feces are not properly contained. However, the risk of exposure to zoonotic pathogens is not well documented. This study was conducted to assess animal handling practices and the risk of childhood diarrhea among rural households in northwest Ethiopia. Methods: This study was done among 403 randomly selected households. Information on animal handling was collected using a questionnaire and spot-check observation. The occurrence of childhood diarrhea in 14 days prior to the survey was assessed based on the reports of female head of households. Multivariable binary logistic regression analysis was performed to identify the association between animal handling practices and childhood diarrhea. Results: All the female head of households had contact with animal feces when preparing fuel disks and plastering the house components with animal dung. Domestic animals shared a corral within the living space of the humans in 20% of the households. Animals entered the human living quarters and accessed foods in 32% of the households. Moreover, 24% of the children aged 24 to 59 months had diarrhea in a 2-week period prior to the survey. Childhood diarrhea was associated with domestic animals sharing the same house as humans (AOR: 3.3, 95% CI: 1.3, 8.6), presence of animal excreta in child playing areas (AOR: 2.4, 95% CI: 1.2, 4.6), contact of domestic animals with stored foods (AOR: 3.5, 95% CI: 2.0, 5.9), trapped dirt under fingernails of female heads (AOR: 3.7, 95% CI: 1.9, 7.5), open defecation (AOR: 3.24, 95% CI: 1.8, 5.9), and unprotected sources (AOR: 4.2, 95% CI: 1.1, 15.3). Conclusion: Domestic animals and their excreta are not hygienically contained in the area. Animal handling practices including their excreta and the hygiene behavior of female head of households (eg, handwashing and food handling practices) should be improved to prevent childhood diarrhea.